Asset securitization : theory and practice - Hu, Joseph (Singapore : John Wiley & Sons (Asia), 2011)
Annotation Asset Securitization is intended for beginners and market professionals alike who are interested in learning about asset securitizationits concepts and practices. It is designed so that the readers will come away with a fundamental but comprehensive understanding of the asset securitization market. As such, the book aims to provide a review of the market's development, necessary framework, potential benefits, and detailed descriptions of major asset securitization products. Part I of the book, which consists of four chapters, will discuss the fundamental concepts, the funding efficiency, the market participants, and the potential benefits of asset securitization. An analysis of mortgage finance will be provided in Part II, which consists of six chapters that cover a variety of topics from the description of many different types of residential mortgages to the securitization of different types of residential mortgages, including the now infamous sub-prime mortgages. Also included are important topics, such as prepayments, cash flow structure, maturity and credit tranching, and the trading and relative value of the various mortgage-backed securities. The three chapters in Part III will explain the other major asset securitization products, such as commercial mortgage-backed securities, credit card receivable-backed securities, auto loan-backed securities, and collateralized bond obligations. Part IV has two chapters: one reviews the collapse and the potential recovery of the asset securitization market, and the other describes the asset securitization efforts in Japan, Australia, Taiwan, and China. Extensive tables and charts are presented to help illustrate a concept or describe a product. Neither analytical discussions nor investment strategies of the various asset-backed securities are included as they are not the focus of this book.
Front Matter -- Basics of Asset Securitization. Asset Securitization: Concept and Market Development -- Originators and Investors of the Asset Securitization Market -- Intermediary Participants of the Asset Securitization Market -- Necessary Ingredients and Benefits of Asset Securitization -- Residential Mortgages and Securitization of Residential Mortgages. Residential Mortgages -- The Residential Mortgage Market -- Residential Mortgage Pass-Through Securities -- Multiclass Mortgage Pass-Throughs -- Private-Label Mortgage Pass-Throughs -- Subprime Mortgage-Backed Securities -- Securitization of Commercial Mortgages and Consumer Loans. Commercial Mortgage-Backed Securities -- Asset-Backed Securities -- Collateralized Debt Obligations -- The Current Asset Securitization Market in the United States and Asia-Pacific. The Collapse and Recovery Prospects of the Asset Securitization Market -- Asset Securitization in Asia-Pacific -- Appendix A: Analysis of Prepayment and Prepayment Rate -- Appendix B: Housing Price Appreciation and Mortgage Credit Performance -- Appendix C: Fundamental Elements in Credit Ratings -- Appendix D: The Collapse of the Asset Securitization Market -- Index.
Includes bibliographical references and index.
Keywords: Asset-backed financing; Asset-backed financing; BUSINESS & ECONOMICS -- Investments & Securities -- General; BUSINESS & ECONOMICS -- Finance; Asset-backed financing; Asset-backed financing; Electronic books